2020
DOI: 10.3892/ol.2020.12254
|View full text |Cite
|
Sign up to set email alerts
|

Thiostrepton and miR‑216b synergistically promote osteosarcoma cell cytotoxicity and apoptosis by targeting FoxM1

Abstract: Osteosarcoma is a common primary bone cancer that there are currently no effective treatment strategies for. Forkhead box M1 (FoxM1) is key in the development of osteosarcoma, and microRNA (miR)-216b serves an antitumor role by targeting FoxM1. Moreover, thiostrepton (TST), a natural thiazole antibiotic, induces antitumor effects and specifically targets FoxM1. Therefore, the present study investigated whether thiostrepton and miR-216b synergistically inhibited osteosarcoma cells by targeting FoxM1. The MTT as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…miRNA 216b was also downregulated in pancreatic cancer tissue and appeared to be related with the inhibition of pancreatic cancer cells proliferation as well as a KRAS-silencing induced apoptosis [ 45 ]. In addition, miRNA-216b could suppress FoxM1 expression in human glioma, osteosarcoma, liver cancer, cervical cancer, melanoma, and NSCLC [ 46 – 51 ]. Some studies demonstrated that miRNA-216b can inhibit lung cancer cell growth via diverse signal pathways [ 6 , 47 , 52 , 53 ] and it was associated with cisplatin sensitivity by modulating autophagy [ 54 56 ] and prognosis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA 216b was also downregulated in pancreatic cancer tissue and appeared to be related with the inhibition of pancreatic cancer cells proliferation as well as a KRAS-silencing induced apoptosis [ 45 ]. In addition, miRNA-216b could suppress FoxM1 expression in human glioma, osteosarcoma, liver cancer, cervical cancer, melanoma, and NSCLC [ 46 – 51 ]. Some studies demonstrated that miRNA-216b can inhibit lung cancer cell growth via diverse signal pathways [ 6 , 47 , 52 , 53 ] and it was associated with cisplatin sensitivity by modulating autophagy [ 54 56 ] and prognosis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-216b has an antitumor role by targeting FoxM1 in OS [96] and suppressing the migratory and invasive potential of cells. In addition, miR-216b expression synergistically inhibits cytotoxicity and stimulates apoptosis in OS cells by increasing Bax expression and decreasing Bcl-2 expression [96]. Low expression of miR-134 was observed in OS cell lines (U2OS, MG63).…”
Section: • Foxm1 Foxm1 (Foxhead Box M1mentioning
confidence: 99%
“…FoxM1 is highly expressed in human OS tissues and cell lines, and downregulation of FoxM1 expression was found to inhibit the viability, migration, and invasive growth of OS cells (Zhu et al, 2020b). Recent studies have shown that avasimibe (Wang et al, 2019a), diallyl disulfide (Li et al, 2018), thiostrepton (Cai et al, 2020), and some miRNAs [including miR-134 (Li et al, 2018), miR-370 (Duan et al, 2015), miR-216b (Wang et al, 2019b), andmiR-197 (Sun et al, 2020)] inhibit the proliferation and invasive growth of OS cells by directly or indirectly downregulating FoxM1 expression.…”
Section: Osteosarcomamentioning
confidence: 99%